2009
DOI: 10.1007/s11418-009-0382-0
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavengers from the aerial parts of Euphorbia petiolata

Abstract: Reversed-phase preparative high-performance liquid chromatography (HPLC) of the methanol extract of the aerial parts of Euphorbia petiolata Banks & Soland, an endemic Iranian medicinal plant, yielded ten free radical scavengers including eight flavonoid glycosides myricetin 3-O-glucoside (1), kaempferol 3-O-(2-O-galloyl)-glucoside (2), myricetin 3-O-rhamnoside (3), quercetin 3-O-glucoside (4), kaempferol 3-O-glucoside (5), quercetin 3-O-rhamnoside (6), kaempferol 3-O-rhamnoside (7), and quercetin 3-O-rutinosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For example, Nazemiyeh et al . [33] reported that this compound has a free radical scavenging ability in animals. This was basically attributed to the existence of a phenolic moiety in the structure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nazemiyeh et al . [33] reported that this compound has a free radical scavenging ability in animals. This was basically attributed to the existence of a phenolic moiety in the structure.…”
Section: Discussionmentioning
confidence: 99%
“…Through of the phytochemical screening were detected alkaloids, flavonoids, and coumarins. Based on the antioxidant activity reported in the literature for alkaloids, flavonoids, and coumarins we can link the presence of these secondary metabolites to the antioxidant activity detected [31, 32]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, sequences from Euphorbia spp. or Manihot esculenta , which accumulate esculetin (Masamoto et al, 2003; Bayoumi et al, 2008a; Nazemiyeh et al, 2009; Shi et al, 2009), showed high similarities. The biosynthetic pathway of simple coumarins containing esculetin in these plants would be elucidated through the functional analysis of these sequences.…”
Section: Quest For the Candidate Sequences Of Ortho-hydroxylases In Pmentioning
confidence: 99%